Single‐shot spiral imaging at 7 T. Issue 5 (25th March 2018) - Engel, Maria; Kasper, Lars; Barmet, Christoph; Schmid, Thomas; Vionnet, Laetitia; Wilm, Bertram; Pruessmann, Klaas P.
Abstract : Purpose: The purpose of this work is to explore the feasibility and performance of single‐shot spiral MRI at 7 T, using an expanded signal model for reconstruction. Methods: Gradient‐echo brain imaging is performed on a 7 T system using high‐resolution single‐shot spiral readouts and half‐shot spirals that perform dual‐image acquisition after a single excitation. Image reconstruction is based on an expanded signal model including the encoding effects of coil sensitivity, static off‐resonance, and magnetic field dynamics. The latter are recorded concurrently with image acquisition, using NMR field probes. The resulting image resolution is assessed by point spread function analysis. Results: Single‐shot spiral imaging is achieved at a nominal resolution of 0.8 mm, using spiral‐out readouts of 53‐ms duration. High depiction fidelity is achieved without conspicuous blurring or distortion. Effective resolutions are assessed as 0.8, 0.94, and 0.98 mm in CSF, gray matter and white matter, respectively. High image quality is also achieved with half‐shot acquisition yielding image pairs at 1.5‐mm resolution. Conclusion: Use of an expanded signal model enables single‐shot spiral imaging at 7 T with unprecedented image quality. Single‐shot and half‐shot spiral readouts deploy the sensitivity benefit of high field for rapid high‐resolution imaging, particularly for functional MRI and arterial spin labeling.